Development of Village Administration Data E-Monography Application - Suci Megawati; Indah Prabawati; Tauran Tauran; Deby Febriyan Eprilianto; M. Noer Falaq Al Amin (Borong Newinera Publisher, 2023)
Utilization and processing of basic village data by the Kedungluk Village Government, Candi District, Sidoarjo Regency, through e-monograph is an effort by the village government to carry out a transformation process to develop an information culture. This study aims to determine the development and design of an application-based information system prototype (village monograph) that provides information and potential as well as village profiles, and provides convenience for village monograph data managers and users. In addition to providing benefits to the village government through the e-monograph application prototype, this research is also expected to contribute to learning in the State Administration Study Program by presenting a learning model that can provide opportunities for students to learn directly (become a laboratory) related to the use of information technology in designing and managing public sector organizations in accordance with the learning outcomes of the fourth study program. The research method used is the Research & Development (R&D) method where one of the models suitable for this research is the SDLC (Software Development Life Cycle) model and specifically the Waterfall model which consists of six stages of software development namely requirements, design, implementation, testing, deployment and maintenance. The output of this research is software or software.